PENINGKATAN KOMPETENSI MASYARAKAT DI KAMPUNG RHEPANG MUAIF, NIMBOKRANG, JAYAPURA DALAM PENGELOLAAN EKOWISATA KAWASAN HUTAN ADAT - Supeni Sufaati; Verena Agustini; Suharno Suharno (JURNAL PENGABDIAN PAPUA, 2017)
Rhepang Muaif village in Nimbokrang, Jayapura, Papua has forest that is good for birdwatching and easily accessible. The local community has already initiated an ecotourism and birdwatching group called Kelompok EkowisataBirdwatching Isyo Hiil’s RhepangMuaif. The main obstacle of that group is that it has no structuralmanagement yet. Therefore, Cenderawasih University as a state university nearby to the area has responsibility to support the management of that group trough the community service program. This program has aim to educate that group on ecosystem of biodiversity and conservation, to empower community on local biodiversity conservation, and also to develop a role model for local community management on ecotourism. Focus Group Discussion (FGD) and Participatory Planning were used to conduct this program. The results showed that the community has good knowledge on the diversity of the flora and fauna of their forest. They also have high awareness on forest conservation and take good care of the forest by local wisdom. A model for local community management on ecotourism has been developed by this activity. All the members of the group were fully participating and very enthusiastic in supporting the program. This program was successfully conducted by the synergy of the university, the head of local village and Kelompok Ekowisata Birdwatching Isyo Hiil’s Rhepang Muaif.Keywords: Ecotourism, conservation, Birdwaching, Isyo Hill’s, Rhepang Muaif,Jayapura